Electroprecipitation of inorganic borates, with different solubility, within monumental stones to avoid fungal colonization. (3rd March 2023) - Feijoo, J.; Gomez-Villalba, L.S.; de los Ríos, A.; Fort, R.
Graphical abstract: Highlights: Protection of stony materials against biodeterioration by ecofriendly compounds. Electroprecipitation of borates of different solubility to increase their applicability. The treatment allows the precipitation of different boron compounds. The treatment is effective in preventing the fungal colonization. The crystallization habit and penetrability differ depending on the material to be treated. Abstract: Biodeterioration is a serious threat to the preservation of cultural heritage. Currently, the chemical treatments used to combat it must fulfil a series of restrictions to ensure that they are not harmful to humans or the environment. Borates satisfy these conditions but due to its high degree of leaching its application is limited to indoor areas. The use of electroprecipitation may to increase the range of applicability by allowing to precipitate, along the entire section of the stony materials, of a mixture of boron salts with different solubility (zinc, magnesium, and sodium borates) to cover a wide range of moisture conditions. The results obtained show that electroprecipitation not only increases the penetration depth of boron compounds but also allows the formation of compounds of different solubility, which allows the treatment to last over time. Furthermore, the treatment increased the mechanical properties and reduced the porosity of the stones treated, all without causing significant aesthetic changes.